Pengelolaan ekosistem mangrove di muara Sungai Musi sebagai upaya mitigasi emisi karbon - Harum Farahisah; Fredinan Yulianda; Hefni Effendi (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2020)
One of the efforts to support the development of coastal areas, is through mangrove management. Besides having a role in the economic development of coastal communities, mangrove also has role as mitigation of carbon emissions. This study aimed to provide an overview of the perceptions and participation of the community and order of stakeholders in the mangrove management at the mouth of Musi River. The research was conducted at Musi River estuary, Banyuasin Regency, South Sumatra Province. Meanwhile, the data of stakeholders perception were derived through respondents' interviews. The results showed that more than 90% of the community knew mangrove existence and function and agreed to participate in various mangrove management policies. An effort is needed so that all stakeholders become key players in mangrove management as carbon reserves at the mouth of the Musi River. Management recommendations for carbon reserves enhancement include empowerment and improvement of community knowledge, forest rehabilitation and land, development of agroforestry cultivation techniques, development of non-timber forests, also soil and water conservation.